Enhancing Curriculum Implementation in Nkowankowa Circuit Secondary Schools: A Qualitative Analysis of Educators' Perceptions in Limpopo-South Africa - Malema Pinny Wisani; Baloyi Gezani (International Journal of Education and Humanities, 2023)
Curriculum implementation in South Africa, particularly in Limpopo Province has many challenges that ultimately affect the quality of education. This study sought to address educators’ perceptions on curriculum implementation in Nkowankowa Circuit secondary schools. Qualitative methods were employed where 16 educators from all eight public schools in Nkowankowa Circuit were purposively sampled on the basis of knowledge and experience on curriculum issues. Face-to-face interviews were conducted to collect data on educator’s perceptions on curriculum implementation. Data collected were analysed by means of thematic data analysis method. The study was conducted from an interpretivist point of view. Findings revealed that proper monitoring enforces effective curriculum implementation, which will improve academic performance. Provision of extra classes also boosts learners’ academic performance. Lack of necessary resources seem to hamper effective implementation. Managing and monitoring curriculum implementation by School Management Teams (SMTs) ensures proper implementation and compliance to policy and improves academic performance. In conclusion, the researcher advanced recommendations that could be implemented at school and circuit level to assist improve implementation of curriculum which will ultimately uplift quality of education and academic performance in schools.